2019
DOI: 10.1039/c9ra02456e
|View full text |Cite
|
Sign up to set email alerts
|

N-doped graphene/CoFe2O4 catalysts for the selective catalytic reduction of NOx by NH3

Abstract: N-doped graphene/CoFe2O4 presented better denitrification activity than CoFe2O4/graphene due to the more uniform distribution of CoFe2O4 and acidic sites etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Figure a displays the graphical comparison between the FE of various metal compounds supported on reduced graphene oxide (rGO) or graphene (G). , ,,, Furthermore, when the yield rates of the graphene- and reduced-graphene-oxide (rGO)-based catalysts are compared to those of other materials, as shown in Figure b (blue bars correspond to graphene-based catalysts, while red bars correspond to the other catalysts reported previously), it is clearly visible that for the rGO- and graphene-based catalysts the yield is much higher. This reflects that rGO- and graphene-based catalysts can be used with requisite properties as catalysts for the NRR. ,,,,,,,,, …”
Section: Fundamentals Of the Nitrogen Reduction Reaction (Nrr)mentioning
confidence: 89%
See 2 more Smart Citations
“…Figure a displays the graphical comparison between the FE of various metal compounds supported on reduced graphene oxide (rGO) or graphene (G). , ,,, Furthermore, when the yield rates of the graphene- and reduced-graphene-oxide (rGO)-based catalysts are compared to those of other materials, as shown in Figure b (blue bars correspond to graphene-based catalysts, while red bars correspond to the other catalysts reported previously), it is clearly visible that for the rGO- and graphene-based catalysts the yield is much higher. This reflects that rGO- and graphene-based catalysts can be used with requisite properties as catalysts for the NRR. ,,,,,,,,, …”
Section: Fundamentals Of the Nitrogen Reduction Reaction (Nrr)mentioning
confidence: 89%
“…This resulted in higher conductivity and redox performance, leading to superior catalyst denitrification activity. Furthermore, the CoFe 2 O 4 /graphene-N catalysts showed improved sulfur and water resistivity compared to CoFe 2 O 4 /graphene catalysts . In another recent report, CoFe 2 O 4 nanoclusters supported by a rGO scaffold were identified as an effective electrocatalyst for the NRR .…”
Section: Fundamentals Of the Nitrogen Reduction Reaction (Nrr)mentioning
confidence: 94%
See 1 more Smart Citation
“…32 Cobalt ferrite (CoFe 2 O 4 ) has inverse spinal structure and is regarded as a widely used catalyst for many organic reactions due to its added advantage of reusability and recovery. 33 Li et al 34 have utilized cobalt ferrite as a catalyst for the NOx conversion, where they loaded CoFe 2 O 4 into graphene (GE) and N-doped graphene (N-GE) as carriers to improve its performance. The results showed that CoFe 2 O 4 /N-GE has sustained a conversion percentage of 95% at a lower temperature of 200-300 ºC because the nitrogen doping allowed a better distribution of the active material with an optimum loading of D r a f t 4%, and the presence of pyridinic nitrogen as active reducing sites which activate the surface more than CoFe 2 O 4 /GE.…”
Section: R a F Tmentioning
confidence: 99%
“…The results showed that CoFe 2 O 4 /N-GE has sustained a conversion percentage of 95% at a lower temperature of 200-300 ºC because the nitrogen doping allowed a better distribution of the active material with an optimum loading of D r a f t 4%, and the presence of pyridinic nitrogen as active reducing sites which activate the surface more than CoFe 2 O 4 /GE. 34 The above studies highlight the need for molecular level investigations into the reactivity of the commercially-available MOFs for their applicability under industrial conditions. Hence, the objective of this study is to systematically investigate the extent of NO reduction when the temperature does not exceed 200 ºC and solid urea is mixed with the MOF as an in situ source of ammonia in a dry environment.…”
Section: R a F Tmentioning
confidence: 99%